A light way for nuclear cell biologists. (27th November 2020) - Forlani, Giada; Di Ventura, Barbara
Abstract: The nucleus is a very complex organelle present in eukaryotic cells. Having the crucial task to safeguard, organize and manage the genetic information, it must tightly control its molecular constituents, its shape and its internal architecture at any given time. Despite our vast knowledge of nuclear cell biology, much is yet to be unravelled. For instance, only recently we came to appreciate the existence of a dynamic nuclear cytoskeleton made of actin filaments that regulates processes such as gene expression, DNA repair and nuclear expansion. This suggests further exciting discoveries ahead of us. Modern cell biologists embrace a new methodology relying on precise perturbations of cellular processes that require a reversible, highly spatially confinable, rapid, inexpensive and tunEable external stimulus: light. In this review, we discuss how optogenetics, the state-of-the-art technology that uses genetically encoded light-sensitive proteins to steer biological processes, can be adopted to specifically investigate nuclear cell biology. Graphical Abstract: